The modulation effects of repeated transcutaneous auricular vagus nerve stimulation on the functional connectivity of key brainstem regions along the vagus nerve pathway in migraine patients - Huang, Yiting; Zhang, Yue; Hodges, Sierra; Li, Hui; Yan, Zhaoxian; Liu, Xian; Hou, Xiaoyan; Chen, Weicui; Chai-Zhang, Thalia; Kong, Jian; Liu, Bo (Frontiers in Molecular Neuroscience, 2023)
Background Previous studies have shown a significant response to acute transcutaneous vagus nerve stimulation (taVNS) in regions of the vagus nerve pathway, including the nucleus tractus solitarius (NTS), raphe nucleus (RN) and locus coeruleus (LC) in both healthy human participants and migraine patients. This study aims to investigate the modulation effect of repeated taVNS on these brainstem regions by applying seed-based resting-state functional connectivity (rsFC) analysis. Methods 70 patients with migraine were recruited and randomized to receive real or sham taVNS treatments for 4 weeks. fMRI data were collected from each participant before and after 4 weeks of treatment. The rsFC analyses were performed using NTS, RN and LC as the seeds. Results 59 patients (real group: n = 33; sham group: n = 29) completed two fMRI scan sessions. Compared to sham taVNS, real taVNS was associated with a significant reduction in the number of migraine attack days (p = 0.024) and headache pain intensity (p = 0.008). The rsFC analysis showed repeated taVNS modulated the functional connectivity between the brain stem regions of the vagus nerve pathway and brain regions associated with the limbic system (bilateral hippocampus), pain processing and modulation (bilateral postcentral gyrus, thalamus, and mPFC), and basal ganglia (putamen/caudate). In addition, the rsFC change between the RN and putamen was significantly associated with the reduction in the number of migraine days. Conclusion Our findings suggest that taVNS can significantly modulate the vagus nerve central pathway, which may contribute to the potential treatment effects of taVNS for migraine. Clinical Trial Registration: http://www.chictr.org.cn/hvshowproject.aspx?id=11101, identifier ChiCTR-INR-17010559.